ASSESSMENT OF THE RATE OF CHANGE IN THE RAPID SHALLOW BREATHING INDEX AND ITS IMPACT ON EXTUBATION OUTCOMES IN MECHANICALLY VENTILATED PATIENTS - RANA, MA; HASSAN , KO; SHOAIB, MI; MOSTAFA, AMH; AWAD , AHA; JAVED, M; MADY, AF; ABDELBAKY , AM; ELMASRY , WG (Biological and Clinical Sciences Research Journal, 2023)
Mechanical ventilation is a crucial intervention in critical care, but weaning and extubation can be complex. Extubation failure poses significant risks, including increased morbidity and mortality. The Rapid Shallow Breathing Index (RSBI) has been explored to predict extubation outcomes. Still, recent research suggests that assessing the rate of change of RSBI over time (ΔRSBI) could enhance prediction accuracy. In this prospective observational study, we analyzed data from patients with respiratory failure, including those with airway diseases and those without documented respiratory conditions. RSBI was measured at the 5th and 120th minutes of spontaneous breathing trials (SBT), and the ΔRSBI was calculated. Patients were categorized into extubation failure and success groups based on their post-extubation outcomes. Receiver-operating characteristic (ROC) curves were generated to determine optimal RSBI thresholds for predicting extubation failure. Out of 119 patients, 23 were excluded due to intolerance to the 120-minute SBT. The remaining 96 patients were divided into normal and airway groups. In the overall analysis, ΔRSBI had an AUC of 0.943, with a threshold of 26% ΔRSBI predicting extubation failure (sensitivity 96%, specificity 91%, overall accuracy 89%). RSBI 120 had an AUC of 0.837, with an optimal threshold of 71 (sensitivity 86%, specificity 78%, overall accuracy 82%). In the normal group, ΔRSBI (AUC 0.785) with a threshold of 24% (sensitivity 86%, specificity 92%, overall accuracy 88%) outperformed RSBI-120 (AUC 0.931) with a threshold of 70 (sensitivity 86%, specificity 91%, overall accuracy 86%). In the airway group, ΔRSBI (AUC 0.893) with a threshold of 26% ΔRSBI (sensitivity 88%, specificity 84%, overall accuracy 88%) and RSBI 120 (AUC 0.863) with a threshold of 76 (sensitivity 88%, specificity 84%, overall accuracy 84%) showed strong predictive capabilities. Assessing the rate of change of RSBI during a 120-minute SBT offers superior predictive value for extubation outcomes compared to a single RSBI measurement. This approach is particularly valuable in patients with airway diseases. Accurate extubation prediction can reduce reintubation rates and associated complications, ultimately improving patient care.